Study on the synthesis and performance of lignin polyether sulfonate surfactants for enhanced oil recovery. Issue 9 (2nd September 2017) - Sun, Hong; Liu, Qiang; Chen, Shuyan; Yan, Xiang; Dai, Lingmei; Zhou, Yujie; Zhang, Jianan
ABSTRACT: Lignin polyether sulfonate surfactants with lipophilic groups of different polymerization degree were synthesized and the dynamic interfacial tension (IFT) between solutions of these surfactants prepared with brine and two kinds of oil from Daqing and Huabei Oilfields was measured, respectively. The results showed that the surfactants were effective in lowering the IFT between brine and the two kinds of oil. The structures of synthesized surfactants were analyzed by Fourier Transform Infrared Spectroscopy (FTIR). The contents and hydrophilic–lipophilic balance values of the lignin polyether sulfonates were studied to evaluate the basic physicochemical properties of the synthesized surfactants. GRAPHICAL ABSTRACT: